Sensory Museology as a Tool for Social Inclusion - Comas Camacho, Carme (Eikón / Imago, 2019)
Museums have changed their main focus of interest, from the object coldly displayed, aiming to reach all variety of audience. The visitor is understood as the addressee, the user and the backbone who must embrace the proposals, while the museum begins to be understood as an open space to socialize, educate, and even for leisure. In recent years, Esplugues Museums have shifted towards an adaptation to the new requirements of museums current context. Through their accessibility program, it has been attempted to place museums on the path of social museology, where have emerged different complementary research branches and lines, such as inclusive, participatory or critical museology, among others. Since 2015, we have established a new discipline, the sensorial museology, leading us to confirm that sensorial activities have a promising approach as a tool for social inclusion.